New research on the Urnfield period of Eastern Slovenia. A case study of Rogoza near Maribor - Matija Črešnar (Arheološki Vestnik, 2010)
The  construction  of  the  motorway  network  in  Slove-nia  uncovered  an  archaeological  site  at  Rogoza,  which became  a  case  study  for  an  Urnfield  period  settlement even  before  it  was  fully  published.  Potter y  and  radio-carbon  dates,  to  some  extent,  indicate  that  the  area  was inhabited  in  other  periods  as  well.  It  yielded  finds  from the  Early  Bronze  Age,  the  Early  Iron  Age,  the  Late  Iron Age  and  the  Roman  period.This  paper  introduces  pottery,  metal  and  stone  finds from the Urnfield period and includes results of analyses of  metal,  stone  finds,  bones  and  plant  remains.  It  also presents the development of the settlement at Rogoza and the Urnfield period settlement patterns in eastern Slovenia, knowledge of which has considerably increased during the last decade, marked by intense archaeological fieldwork.